An assessment of the interaction for three Chrysanthemum indicum flavonoids and α‐amylase by surface plasmon resonance. Issue 1 (16th December 2019) - Li, Pao; Huang, Zhao; She, Yin; Qin, Si; Gao, Wanru; Cao, Yanan; Liu, Xia
Abstract: This study evaluated the interaction of Chrysanthemum indicum (CI) flavonoids (luteolin, acacetin, and buddleoside) with α‐amylase. Surface plasmon resonance (SPR) assay showed their equilibrium dissociation constants ( KD ) are 1.9695 ± 0.12, 2.9240 ± 0.20, and 3.2966 ± 0.08 mM at pH 6.0, respectively. Furthermore, their binding affinities were influenced by KCl, MgCl2, and CaCl2 . Enzymatic kinetic studies revealed that three flavonoids exhibited noncompetitive α‐amylase inhibitory activity. The inhibitory sequence is luteolin > acacetin > buddleoside, which was in accordance with the results of binding affinity from SPR. 1, 1‐diphenyl‐2‐picryl hydrazyl radical assay demonstrated that antioxidant activities of three flavonoids were inhibited significantly with α‐amylase. Meanwhile, the study reveals that hydroxyl on C′‐4, C′‐5, and C‐7 of flavonoids play an important role on the interaction of three flavonoids with α‐amylase. Also, SPR could be used as sensor for rapid screening inhibitors of α‐amylase and provide useful information for the application of C. indicum flavonoids in food and pharmaceutical area. Abstract : In this work, the kinetic constants, structure‐activity relationship, and influence factors of flavonoids and α‐amylase interaction were revealed. α‐Amylase activity and flavonoids antioxidant abilities were examined after interaction of flavonoids with α‐amylase.